Материалы по фауне конопид (Diptera, Conopidae) Крыма - Зимина, Л.В. (Вестник зоологии, 1967)
For the first time the Crimean conopids are observed. 38 species of conopids are registered in the Crimea, 49 — in the Caucasus, 50 — in the European part of the USSR (table 3). The lists of Hymenoptera (table 1) on which these conopids parasitize and plants, including the melons, which are visited by conopids, are presented in this article. Four species or Conopidae of the Mediterranean origin are the most usual for the Cri-mea: Physocephala pusilla, Ph. vittata, Thecophora melanopa and T. pusilla. Six species — Physocephala curticornis, Ph. lacera, Ph. truncata, Myopa morio, Leopoldius sig-natus, Sicus abdominalis — are pointed out for the first time in the Ukraine. Thus nowadays on the territory of the Ukraine 48 species of Conopidae are registe-red according to the literary and the author's own data.